Analysis of Cooperative Unions’ Development Case Study: Poland - Bednarz, Joanna (Communications - Scientific letters of the University of Zilina, 2005)
Cooperative unions in Poland are self-aid communities acting on the market of financial services. They gather people connected by the same working place or membership in the same community or professional group, who save together and lend money one another. They play an important economic role in Poland because of the fact that they are servicing people who because of their unfavourable or unstable financial condition could not be clients of commercial banks, and in this way would be denied the access to certain financial services, mainly to credits. In the presented article the quick development of the cooperative unions in Poland is presented.